Pemodelan Spatial Error Model (SEM) Untuk Mengidentifikasi Indeks Pembangunan Manusia di Provinsi Maluku Tahun 2016 - Fauzan Samallo; Yopi Andry Lesnussa; Abraham Z. Wattimena; Muhammad Yahya Matdoan (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2018)
Human Development Index (HDI) is a quality measure that can be used to determine the quality of human development that has been achieved. HDI is a composite index that composed of 3 components, such as: Length of life measured by life expectancy at birth, Education measured by average school duration and expectations school duration and standard of living measured by Purchasing Power Parity (PPP) in rupiah. The model used in this research is Spatial Error Model (SEM) to identify Influence of Variables X on IPM value and pattern of HDI distribution in a region with Ordinary Linear Square (OLS) parameter estimates. From the map thematic data that obtained, it can be seen that the pattern of the spread of Human Development Index (HDI) in Maluku Province has no effect on the distance of a region. There is a correlation between the components of HDI compilers to the HDI value in Maluku Province, because there is a spatial dependency on the dependent variable. Lambda value coefficient which is negative and significant at ? = 10% indicates that there is no correlation of HDI value in a region with other adjacent area. Also indicated by spatial residuals in adjacent areas do not have the same characteristics.